PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Fitri Wulandari Fauzi; Tri Jalmo; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Observation result at X class of SMA N 3 Kotabumi, known that the result of students learning still low. A solution is needed to improve student’s learning activity and result that is PBL models. The objectives of this research were know the influence of PBL in improve students learning activities and result. This research is a quasi experiment with pretest-posttest nonequivalent. The sample was students at X9 and X8 which was chosen with purposive sampling. The quantitative data gattered from pretest, posttest, and N-gain score which was analyzed by t-test. The qualitative data in form of description activities and questionnaire of students response on the using of PBL models. The result of students learning activities are in average of high criteria. The result of students learning was increase, with N-gain average (0,58). Then the result of questionaire shows that all of the students gives positive response with PBL model. Thus, PBL model has a effect on student learning activities and result.  Keywords: learning activities, PBL models, pollution and conservation of environmental, result of learning.